Efektivitas Pendekatan Pembelajaran Berbasis TPACK untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA di SDN 2 Sugih Waras - Gunawan, Guntur; Faningsi, Sri; Asha, Lukman; Yumiarty, Yuyun (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
The aims of this research are 1). Analyzing initial abilities in the experimental class and control class, 2). Analyzing the influence of the TPACK-based learning approach on learning outcomes, 3). Analyzing the effectiveness of a TPACK (Technological Pedagogical Content Knowledge) based learning approach in class III at SDN 2 Sugih Waras. This research is quantitative research with a true experimental design experimental method. The research data collection technique used pretest and posttest, research samples were students in class III A, experimental class and III B, control class. The data analysis technique used was a prerequisite test, data analysis used the independent sample t test and the N-Gain test. Based on research results 1). Sig value. (2-tailed) from the pretest data of experimental class and control class students, namely 0.562 > 0.05. This shows that Ho is accepted, meaning there is no difference in the average initial ability of students in the experimental class and the control class, 2). There is an influence of the TPACK-based learning approach on learning outcomes. This can be seen based on the t test table which shows the Sig value. (2-tailed) is 0.00 < 0.05, then Ho is rejected and Ha is accepted, 3). The results of the N-Gain test in class III A which used TPACK got an average score of 62.41 which was categorized as quite effective, while in class III B which used the lecture and assignment method the average was 22.77 which was categorized as ineffective.